2010
DOI: 10.1038/ejcn.2010.227
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of the effect of school food and dining room modifications on classroom behaviour in secondary school children

Abstract: Background/Objectives: Adequate nutrition is considered important for learning, but there is little robust research on the association between diet and learning in school-aged children in industrialized countries. This study investigated the effect of tailored modifications to the food and dining experience in secondary schools on learning-related behaviours. Subjects/Methods: In 2008, 12 co-educational secondary schools in England were recruited. Schools were randomly allocated to receive a tailored action pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 32 publications
1
42
0
1
Order By: Relevance
“…Not only will the choice of food affect health but where improvements have been made to lunchtime food, there is some evidence to suggest this has led to an increase in pupils' concentration during the afternoon session (4,5) .…”
mentioning
confidence: 99%
“…Not only will the choice of food affect health but where improvements have been made to lunchtime food, there is some evidence to suggest this has led to an increase in pupils' concentration during the afternoon session (4,5) .…”
mentioning
confidence: 99%
“…Classroom behavior is dynamic and can be different across year groups and ages. Previous research has found differences in behavior between older and younger children in the classroom following school lunch manipulations, where younger children tend to be more distracted when working alone with the reverse true for older children and adolescents (Golley et al, 2010;Storey et al, 2011). The influence of gender on behavior is also not considered by most studies.…”
Section: Methodological Issuesmentioning
confidence: 87%
“…There is a lack of studies that use systematic, validated, and reliable coding systems to measure classroom behavior. Two recent studies have demonstrated effects on on-task behavior following school lunch manipulations using a validated observation protocol (Golley et al, 2010;Storey et al, 2011). Future studies investigating the effects of breakfast on behavior should adopt validated and reliable, focused coding schemes to measure classroom behavior.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Several studies on adolescent breakfast skipping attributed this phenomenon to lower socioeconomic status, food deprivation urbanization, long use of cell-phones and other electronic devices especially at night (Burghardt and Devaney, 1995;Hoyland et al, 2012;Pereira et al, 2011;Utter et al, 2007). Adolescents and children are still dependants and they need adequate attention and care in order for them to be able to develop meals and food habits that are healthy and will promote good nutritional status (Lazzeri et al, 2013;Nanney et al, 2011;Storey et al, 2011;Wate et al, 2013). Skipping breakfast and unhealthy food consumption may lead to micro nutrients deficiencies and poor nutritional status (Acham et al, 2012;Hallstrom et al, 2013;Pereira et al, 2011;So et al, 2011).…”
Section: Introductionmentioning
confidence: 99%